A compreensão do corpo na formação profissional do fisioterapeuta - Meyer, Patrícia Froes (2005)
Physical therapy has suffered of a mechanistic influence, with the superspecialization and fragmentation of learning, which interfers directly in the professional s understanding of the body, besides affecting his therapeutic performance. Worried about this reality, this research analyzed perceptions of Physical therapy students from Universidade Federal do Rio Grande do Norte and Universidade Potiguar about the human body. This is a descriptive study where 167 students were evaluated through objective and subjective responses to questionnaires designited QUEB Questionnare of understanding body evaluation. Searching the complement of the datas the QUEB open-ended was created, which gives freedom to students to answer freely. This questionnnaire was applicated on a subgroup composed by 21 students of the Health Sociology subject of the Physical therapy course. The validation process of these questionnaires included strategies of a panel of experts and face validity. The theorical reference analyzed based on the studies which favor the rejoining of knowledge represented by transdisciplinary support. The analysis of the results were performed quantitativavely and qualitatively through categorization of the responses selectioning key-words and the most expressive discourses , besides using descritive statistics interpretation. According to the responses, the body thought only thought biologically, ignoring the understanding of man as a cultural and social construction, confirming the presence of the reductionist model, with overvalorization of early specialization, technical training and purely biological and mechanical considerations of the body and its mobility. Probably, the dialogic knowledge of the body human inside Physical Therapist s learning can promote a growth of health s concept and a true activeness of Physical therapy on it, being the body a link with social environment. So, through understanding of the body as a complex form, the physical therapy will be able to attend your patients considerating their biological characteristics, but so the religious, political, social and ethics. Finally, this reflection suggests a search for a less technical vision, which allows the professional to discern more than segments of the body and which will contribute to a wider understanding of the patient and his social context, leading to greater humanization of the body , improvement in services and consequently, in the quality of life of these patients